Studies in Chinese Tettigoniidae: Recent discoveries of Meconematinae katydids from Xizang,China (Tettigoniidae: Meconematinae) - Wang, Hanqiang; Liu, Xianwei (Zootaxa, 2018)
In this work, we describe one new genus and 4 new species from Xizang, China: Allogrigoriora carinata gen & sp. nov., Nigrimacula beybienkoi sp. nov., Sinoxizicus carinatus sp. nov. and Tamdaora curvicerca sp. nov. Besides the new taxa, 3 new combinations [Grigoriora cheni (Bey-Bienko, 1955) comb. nov.; Grigoriora kweichowensis (Tinkham, 1944) comb. nov.; Nefateratura bifurcata (Liu & Bi, 1994) comb nov.] are also changed. All the specimens are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences.